Commute happiness in Xi'an, China: Effects of commute mode, duration, and frequency. (April 2018) - Zhu, Jing; Fan, Yingling
Highlights: Commute happiness is associated with commute mode and duration, but not frequency. Employer shuttle bus is the happiest mode, followed by private bike and walking. People who use regular city buses reported the lowest commute happiness. Subway, public bike, and electric bike show no differences in commute happiness from car. Longer commute duration is associated with lower happiness. Abstract: Commuting between home and work is an important aspect of everyday life. Based upon the broaden and build theory of positive emotions, experiencing happiness during commutes generates positive emotions that are beneficial for both individual and societal well-being. The existing literature on commute happiness is dominated by studies from the U.S., Canada, and Europe. Little is known about commute happiness in Chinese cities where electric bikes and employer-provided shuttle buses are common commute modes. This study uses original survey data collected from Xi'an, China to examine how commute happiness may differ across eight commute modes (walk, private bike, public bike, bus, subway, electric bike, shuttle bus, and private car) and by commute duration and frequency, while controlling for personal demographics and overall health and well-being. Results show that commute mode and duration are significantly associated with commute happiness while commute frequency is not. People who use employer shuttle buses reported the highest commute happiness, followed by people who use private bikes and then people who walk. People who use regular city buses reported the lowest commute happiness. People who use subway, public bikes, and electric bikes show no differences in commute happiness from car users. Longer commute duration is associated with lower happiness. Recommendations for Chinese cities to promote commute happiness include improving public bus services, investing in pedestrian and bicycle infrastructure, enhancing bike-transit integration, encouraging employer shuttle bus programs, and fostering jobs-housing balance. The results also indicate a gender gap in commute happiness that merits additional research.